A Study of Students' Difficulties and Conceptual Understanding of the Qualitative and Quantitative Analysis of Organic Compound Elements - Khoirunnisa, Fitriah; Hendrawan; Kadarohman, Asep; Anwar, Sjaeful; Pratiwi, Amelinda (Universitas Pendidikan Ganesha, 2024)
The study examines the learning difficulties and understanding of concepts faced by 28 chemistry students in organic compound element analysis courses using the RADEC learning model. The results showed a moderate increase in understanding. Still, several factors contributed to the low understanding, such as 28% of students reporting difficulty with Kjeldahl material, 24% with Dumas topics, 5% with Lassaigne destruction topics, 9% with Kjeldahl and Dumas topics, and 5% with digestion, distillation, and titration. Additionally, 24% of students did not understand the meaning of the questions, the lecture material's delivery, and the writing of reaction equations. Lack of preparation, such as reading before lectures, also contributed to low understanding.